(untitled) - Peter Sykes (London, 1995)
The book marks a significantly different approach to mechanism in organic chemistry. It is based on three underlying principles: that there are three types of reaction - substitution, addition and elimination; three types of reagent - nucleophiles, electrophiles and radicals; two effects - electronic and steric - through which the behaviour of a particular atom or group can be influenced by the rest of the molecule of which it is a constituent part. An introductory chapter on basic principles is followed by separate chapters exemplifying each type of reaction initiated by each type reagent. Examples of reactions are used throughout to illustarte the theory, and the careful arrangement of rewaction schemes helps to maximize the clarify of the text. End-of-chapter summarizes reinfirce the comprehension of the key points
Keywords: chemistry, organic